Strategi Pemberdayaan Masyarakat Melalui UMKM Kelompok Wanita Tani Kenanga Desa Tanjung - Tasya Kamilannisa; Enjang Suherman; Laras Ratu Khalida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Women Farmers Group is also a forum for self-development for working age women, especially housewives in Tanjung Village, Banyusari District. The Kenanga Women's Farmers Group (KWT) received assistance and assistance from the UPTD of the Banyusari District Agriculture Service and PT. Pertamina. Assistance from the Banyusari District Agriculture Service. The products produced by KWT Kenanga vary, such as herbal food and herbal drinks. The informants in this research were the chairman of KWT Kenanga, members of KWT Kenanga, and the Tanjung Village Community. Based on the research results, the strengths of KWT Kenanga are greater than its weaknesses, namely the overall strength coefficient value is 2.27 and its weaknesses are 1.67 in IFAS, so KWT Kenanga's opportunities are also greater than its threats. According to EFAS, the overall score is 3.14 for opportunities and 1.24 for threats. Based on the results, the SWOT chart of KWT Kenanga indicates its position in quadrant I, indicating a highly favorable situation. The strategy applied in the first quadrant supports an aggressive growth policy (growth-oriented strategy). The situation at KWT Kenanga reinforces the SO strategy, which leverages internal strengths by exploiting external opportunities.